University Tutoring with Artificial Intelligence - Valero-Ancco, Vidnay Noel; Pari-Orihuela, Miryam; Calsin-Chambilla, Yobana Milagros (Journal of Posthumanism, 2025)
The integration of artificial intelligence (AI) tools in education has raised significant interest in student satisfaction. This study aimed to assess university students’ satisfaction with a personalized AI tool. A descriptive study involving 124 students was conducted using a satisfaction survey. Findings showed that 59.7 % of students were very satisfied and 40.3 % were satisfied, emphasizing the tool’s effectiveness in addressing academic queries and generating quality content. However, a key limitation was limited access to AI due to poor connectivity and lack of technological devices. Despite this, the results indicate that AI holds strong potential to improve the educational experience. The study highlights the importance of addressing access barriers to fully leverage the benefits of AI. Overall, it contributes to the educational field by offering insights into students’ perceptions, which can inform future applications and enhancements of AI tools in academic settings.